Novel (Sm0.2Lu0.2Yb0.2Y0.2Dy0.2)3TaO7 high-entropy ceramic for thermal barrier coatings. Issue 6 (15th March 2023) - Sang, Weiwei; Zhang, Hongsong; Zhang, Haoming; Liu, Xuhe; Chen, Xiaoge; Xie, Wenbo; Hou, Ruiyi; Ma, Hongjun; Li, Siqi; Wang, Nan; Li, Xiaolong
Abstract: A novel (Sm0.2 Lu0.2 Dy0.2 Yb0.2 Y0.2 )3 TaO7 (SLT-5RE0.2 ) oxide with a single-fluorite structure was synthesized via an optimized sol-gel and sintering method, and its crystal structure, mechanical and thermophysical properties were investigated. The results indicate that the calcined nanoscale powder is of high crystallinity, and bulk sample is of a uniform elemental distribution. Compared to YSZ (6–8 wt.% Y2 O3 partially stabilized by ZrO2 ), SLT-5RE0.2 exhibits lower Young's modulus, less mean acoustic velocity, and higher Vickers microhardness. Owing to the strengthened anharmonic vibration and phonon scattering, SLT-5RE0.2 exhibits low thermal conductivity (1.107 W K −1 ·m −1, 900 °C). The high thermal expansion coefficient (11.3 × 10 −6 K −1, 1200 °C) of SLT-5RE0.2 ceramic can be ascribed to the reduced lattice energy and ionic spacing as well as the cocktail effect of high-entropy ceramics. The excellent mechanical and thermophysical properties, and excellent phase steadiness during the whole testing temperature cope, indicate that SLT-5RE0.2 high-entropy ceramic can be a candidate material for thermal barrier coatings.